Download presentation
Presentation is loading. Please wait.
Published byDorcas Priscilla Porter Modified over 9 years ago
1
Instructions for using this template. Remember this is Jeopardy, so where I have written “Answer” this is the prompt the students will see, and where I have “Question” should be the student’s response. To enter your questions and answers, click once on the text on the slide, then highlight and just type over what’s there to replace it. If you hit Delete or Backspace, it sometimes makes the text box disappear. When clicking on the slide to move to the next appropriate slide, be sure you see the hand, not the arrow. (If you put your cursor over a text box, it will be an arrow and WILL NOT take you to the right location.)
2
Jeopardy Choose a category. You will be given the answer. You must give the correct question. Click to begin.
3
Choose a point value. Choose a point value. Click here for Final Jeopardy
4
Add, Subtract, Multiply, & Divide Functions Inverses 10 Point20 Points30 Points40 Points50 Points10 Point 20 Points 30 Points40 Points50 Points30 Points 40 Points 50 Points 12 Basic Functions Transformations Composition Of Functions
6
Jeopardy Board 3
7
Which of the 12 basic functions have even symmetry? HINT: There are 3!
8
Jeopardy Board
9
Which of the 12 Basic Functions have ODD symmetry? HINT: There are 4!
10
Jeopardy Board
11
Which 2 of the 12 basic functions are exactly the same just shifted horizontally?
12
Jeopardy Board
13
What is the name of this function, and where are its horizontal asymptotes?
14
Asymptotes at y=1 and the x-axis Jeopardy Board
15
Let f(x) = 3x and g(x) = 5x – 9. Find (f + g)(x)
16
Jeopardy Board (f + g)(x) = 8x - 9
17
Perform the requested operation:
18
Jeopardy Board
19
Perform the requested operation:
20
Jeopardy Board
21
Let f(x) = 1-x 2 and g(x) = 1-x. Find (f g)(x)
22
(f g)(x) = 1 - x - x 2 + x 3 Jeopardy Board
23
Find (f – g)(x) and (f + g)(4) for f(x) = 4x 2 -5x+2 and g(x) = 4+2x+2x 2
24
(f – g)(x)= 2x 2 -7x-2 (f + g)(4) = 90 Jeopardy Board
25
The function f(x) = (x – 3) 2 +4 is the basic function f(x) = x 2 translated how?
26
Right 3 units and up 4 units Jeopardy Board
27
Fill in the blanks to complete the statement: The graph of y = e (x+6) -5 can be obtained from the graph of y = e x by shifting horizontally ? units to ? and shifting vertically ? units to the ? direction.
28
6; left; 5; downward Jeopardy Board
29
Give the equation of the function g whose graph is descibed: The graph of is reflected across the x-axis
30
Jeopardy Board
31
If is reflected about the y-axis, what is the new function?
32
Jeopardy Board
33
Rewrite the basic square root function as if it were shifted 8 units to the left and 3 units up.
34
Jeopardy Board
35
Given f(x) = e x and g(x) = x + 6, Find f(g(x))
36
Jeopardy Board f(g(x)) = e x+6
37
Given f(x) = x 5 and g(x) = -5 + x, Find (g f)(x)
38
2 - 3x 3 Jeopardy Board
39
Perform the requested operation: f(x) = 4x 2 + 4x + 8 g(x) = 4x – 3 Find g(f(x))
40
g(f(x)) = 16x 2 + 16x + 29 Jeopardy Board
41
If f(x) = x 4 and g(x) = 1- 2x 2, find g(f(x))
42
1 – 2x 8 Jeopardy Board
43
zz Given and g(x) = x 2 + 4, find (g f)(6)
44
Jeopardy Board
45
The functions f(x) and g(x) are inverses. Draw a function map that clearly organizes the relationships between the functions, their inputs and outputs.
46
Jeopardy Board 1 2 -2/3 1 - 2/3 2
47
Find the equation of the Inverse function of: f(x) = 3x + 4
48
Jeopardy Board
49
Graph the inverse: f(x) = 3x - 1
50
Jeopardy Board
51
Find the inverse of the function:
52
f -1 (x) = 4(x + 8) 3 Jeopardy Board
53
IF: Confirm algebraically that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x
54
Jeopardy Board
55
Final Jeopardy Make your wager
56
Graph the function: a.Use keywords and complete sentences to explain how to obtain your graph from the twelve basic functions. b.On what intervals is the function’s graph increasing? Decreasing? Constant? c.Is the graph even, odd, or neither? d.Is the graph bounded above, bounded below, bounded, or unbounded?
57
USE ONLINE GRAPHING TOOL a.The function f(x) = ln(x) is reflected about the x-axis and then added to the function f(x) = x b.The function is decreasing on (0, 1) and increasing on (1, ∞) c.The graph is neither even nor odd d.The graph is bounded below because there is a minimum
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.